2005
DOI: 10.1385/endo:26:1:033
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation Block by <I>Pueraria mirifica</I>: A Study of Its Endocrinological Effect in Female Monkeys

Abstract: Pueraria mirifica (PM), a Thai herb containing phytoestrogens, may act as estrogen and disturb reproduction. To investigate the effect of PM on the menstrual cycle length and related hormones, nine adult female monkeys (Macaca fascicularis) were separated into three groups. Each group (n = 3) was fed with 10, 100, and 1000 mg/d of PM for three menstrual cycles. The menstrual cycle length increased significantly in monkeys treated with PM-10 and PM-100 and disappeared completely in monkeys treated with PM-1000.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
20
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 24 publications
2
20
1
Order By: Relevance
“…Treatment with the plant extract at high doses 600 and 800 mg/kg BW, for 30 days induces micronucleus formation in male rats [6]. However, pretreatment of weanling rats with P. mirifica powder at a dose of 10, 100 and 1,000 mg/kg BW for 28 days resulted in a dose-dependent prevention of mammary tumors induced by 7, 12-dimethylbenz (a) anthracene (7, 12-DMBA) [7].The phytoestrogens of P. mirifica exhibit the following responses: dose-dependent estrogenic effects on the reproductive system, initiated vaginal cornification, increased uterine weight with decreased follicle stimulating hormone (FSH) and luteinizing hormone (LH) serum levels in ovariectomized rats [8], increased length of the follicular phase and total menstruation cycle [9], decreased estrogen, progesterone, FSH, and LH concentrations at the dose of 1,000 mg/kg BW [10], and ovulation blockage in female monkeys [11]. In aged menopausal monkeys, consumption of crude powder from the plant decreases the concentrations of FSH and LH [12] and parathyroid hormone (PTH) [13] and induces reappearance of sexual skin [14].…”
mentioning
confidence: 99%
“…Treatment with the plant extract at high doses 600 and 800 mg/kg BW, for 30 days induces micronucleus formation in male rats [6]. However, pretreatment of weanling rats with P. mirifica powder at a dose of 10, 100 and 1,000 mg/kg BW for 28 days resulted in a dose-dependent prevention of mammary tumors induced by 7, 12-dimethylbenz (a) anthracene (7, 12-DMBA) [7].The phytoestrogens of P. mirifica exhibit the following responses: dose-dependent estrogenic effects on the reproductive system, initiated vaginal cornification, increased uterine weight with decreased follicle stimulating hormone (FSH) and luteinizing hormone (LH) serum levels in ovariectomized rats [8], increased length of the follicular phase and total menstruation cycle [9], decreased estrogen, progesterone, FSH, and LH concentrations at the dose of 1,000 mg/kg BW [10], and ovulation blockage in female monkeys [11]. In aged menopausal monkeys, consumption of crude powder from the plant decreases the concentrations of FSH and LH [12] and parathyroid hormone (PTH) [13] and induces reappearance of sexual skin [14].…”
mentioning
confidence: 99%
“…Feeding PM powder suspended in water to ovariectomized rats induces proliferation of the vaginal epithelium and uterus endometrium and reduces the levels of serum follicle-stimulating hormone (FSH) and luteinizing hormone (LH) [7,8]. Reduction of the levels of FSH and LH has also been observed in adult cyclic and aged menopausal female monkeys [9][10][11][12]. PM suppresses folliculogenesis and ovulation in adult cyclic female monkeys after a single or long-term feeding [9,10].…”
mentioning
confidence: 99%
“…Reduction of the levels of FSH and LH has also been observed in adult cyclic and aged menopausal female monkeys [9][10][11][12]. PM suppresses folliculogenesis and ovulation in adult cyclic female monkeys after a single or long-term feeding [9,10]. Intake of crude P. mirifica powder can relieve climacteric symptoms, such as hot flashes, frustration, sleep disorders and skin dryness in post-menopausal women [13].…”
mentioning
confidence: 99%
“…(PM), a Thai herbal plant, belongs to family Leguminosae [5][6][7]. The PM root has been analyzed and found to contain many phytoestrogens, including isoflavone genistein, daidzein, and coumestrol [5].…”
mentioning
confidence: 99%
“…PM influences the reproductive system by reducing serum gonadotropin levels and increasing uterine weight and vaginal cornification in rats [8]. Our previous studies have found that daily treatment with PM induces suppression of serum follicle stimulating hormone (FSH), l u t e i n i z i n g h o r m o n e ( L H ) , e s t r a d i o l , a n d progesterone in adult female cynomolgus monkeys (Macaca fascicularis) in a dose-dependent manner [6], but also that treatment with a single dose of PM has no effect on these hormones [7]. Reduction of serum gonadotropin and sex steroid hormone levels from long-term PM treatment implies disturbance of folliculogenesis and ovulation in monkeys.…”
mentioning
confidence: 99%